(untitled) (Bangladesh Journal of Medicine, 2023)
Atherosclerotic renal artery stenosis is the leading cause of reno-vascular hypertension and is prevalent in elderly patients (over 65 years) and those with resistant hypertension. This article presents a case report of a 60-year-old gentleman who presented with resistant hypertension resulting in heart failure and significant morbidity. The patient’s medical history included frequent hospitalizations with uncontrolled hypertension, flash pulmonary edema and heart failure. Despite multiple hospitalizations, the underlying cause of his condition remained unrecognized until further investigation revealed left sided renal artery stenosis as the culprit lesion. Successful renal artery angioplasty resulted in the resolution of the patient’s high blood pressure and improvement of general well-being. This case highlights the potential for resistant hypertension due to renal artery stenosis to be overlooked, particularly in patients with multiple comorbidity. It is important to consider the possibility of renal artery stenosis in patients with uncontrolled blood pressure with recurrent pulmonary oedema, not responding to multiple anti-hypertensive drugs in the highest possible dose. Bangladesh J Medicine 2023; 34(2): 163-167